Современная и прогностическая оценка численности и распределения большого баклана (Phalacrocorax carbo sinensis) на водоемах Азово-Черноморского побережья Украины - Сиохин, В.Д.; Костюшин, В.А. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2008)
Over the last years (1976-2008) breeding settlements of the Cormorant at the Azov-Black Sea coast of Ukraine and within adjacent areas are connected with 17 natural territorial complexes. Five of these areas are in frame of the natural-reserve fund (Danube and Black Sea Biosphere Reserves, Crimean Natural Reserve, Regional Landscape Parks "Kinburn Spit" and "Meotida"). Nine areas have status of wetlands of the international importance (Dniester Delta, Dnieper Delta, Dzharylgachskiy Bay, Central and Eastern Sivash, Molochnyi Liman, Obitochnaya Spit and Obitochny Bay, Berdyanskaya Spit and Berdyanskiy Bay, upper waters of Kakhovskoe reservoir). Two more territories include areas of Kerch Peninsula and the western coast of the Sea of Azov.